A survey of Euphorinae (Hymenoptera: Braconidae) of southern Iran, with description of a new species - Ameri, Ali; Talebi, Ali Asghar; Rakhshani, Ehsan; Beyarslan, Ahmet; Kamali, Karim (Zootaxa, 2014)
A faunistic survey of Euphorinae (Hym., Braconidae) in southern Iran, as well as an updated checklist of the genera and species in Iran, are presented. Sampling was performed using Malaise traps at different locations of Hormozgan province and Qeshm Island in Persian Gulf during 2011–2013. In total, 38 species belonging to 10 genera are listed from Iran. The recorded species belong to the following genera: Allurus Forster, 1862 (two species), Chrysopophthorus Goidanich 1948 (one species), Dinocampus Forster, 1862 (one species), Ecclitura Kokujev, 1902 (one species), Leiophron Nees von Esenbeck, 1819 (10 species), Meteorus Haliday, 1835 (12 species), Perilitus Nees von Esenbeck, 1819 (five species), Syntretus Forster 1862 (three species), Wesmaelia Foerster, 1862 (one species) and Zele Curtis, 1832 (two species). Allurus lituratus (Haliday 1835), Dinocampus coccinellae (Schrank, 1802), Leiophron (Peristenus) grandiceps (Thomson 1892), Meteorus rubens (Nees, 1811) and Wesmaelia petiolata (Wollaston, 1858) are new records for Hormozgan province and Leiophron (Peristenus) grandiceps (Thomson 1892) is recorded for the first time from Iran. In addition, Meteorus breviterebratus Ameri, Talebi & Beyarslan sp. n. is newly described and illustrated.